2018
DOI: 10.1149/2.0081815jes
|View full text |Cite
|
Sign up to set email alerts
|

Understandings on the Inhibition of Oxygen Reduction Reaction by Bromide Adsorption on Pt(111) Electrodes at Different pH Values

Abstract: Oxygen reduction reaction (ORR) is studied on Pt(111) in the presence of different concentrations of bromide anions at different pH values ranging from very acidic to neutral solutions. While adsorbed bromide inhibits the ORR, the strength of the inhibition decreases when the pH is increased. This is a consequence of the lower relative adsorption energy of bromide at higher pH values, caused by the lower absolute applied potential. This is reflected in a shift of the onset of the ORR (as measured with the hang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 43 publications
2
21
1
Order By: Relevance
“…(Hsueh et al, 1983), halides (Cl − and Br − ) (and Marković et al, 1999; Schmidt et al, 2001; Stamenkovic et al, 2001) and other impurities (P43-, NH4+, CO, SO 2 , H 2 S, etc.) (Macia et al, 2004; Stamenkovic et al, 2005; Halseid et al, 2008; He et al, 2010; Ong et al, 2013; Rahul et al, 2015; Briega-Martos et al, 2018). Therefore, strongly adsorbing anions/cations/impurities/ in situ generated adsorbed species on the catalyst surface interfere with the investigation of dissolution and reconstruction of nanoparticles, making it is hard to investigate the stability, origin of the loss of ESA, and catalytic activity of nanoparticles.…”
Section: Non-recoverable Esa Losses With Halide Ion Adsorption and Acmentioning
confidence: 99%
“…(Hsueh et al, 1983), halides (Cl − and Br − ) (and Marković et al, 1999; Schmidt et al, 2001; Stamenkovic et al, 2001) and other impurities (P43-, NH4+, CO, SO 2 , H 2 S, etc.) (Macia et al, 2004; Stamenkovic et al, 2005; Halseid et al, 2008; He et al, 2010; Ong et al, 2013; Rahul et al, 2015; Briega-Martos et al, 2018). Therefore, strongly adsorbing anions/cations/impurities/ in situ generated adsorbed species on the catalyst surface interfere with the investigation of dissolution and reconstruction of nanoparticles, making it is hard to investigate the stability, origin of the loss of ESA, and catalytic activity of nanoparticles.…”
Section: Non-recoverable Esa Losses With Halide Ion Adsorption and Acmentioning
confidence: 99%
“…Furthermore, the onset potential in the presence of Brshifts to more positive potential values as pH increases. Additionally, measurements for the HPRR in the same conditions were carried out ( Figure 2B) [18]. In all cases the jlim measured for the ORR is higher than the sum of the theoretical jlim for a 2-electron process and the measured current for the HPRR.…”
Section: Experimental Evidences Of a Bifurcation Point In The Orr Mecmentioning
confidence: 90%
“…3. Analogous experiments for HPRR with a H2O2 concentration that would lead to the same limiting current densities were performed, but in this case no decrease of jlim was observed ( Figure 2A) [ The mechanism of the ORR was also studied by investigating the effect of the presence of Brin working solutions with different pH values [18]. It was observed that at very acidic pH values (below pH = 1) the presence of Brreduces the jlim to the half of its theoretical value.…”
Section: Experimental Evidences Of a Bifurcation Point In The Orr Mecmentioning
confidence: 98%
See 2 more Smart Citations